Administration and management in criminal justice: a service quality approach - Allen, Jennifer M. (Sage Publ., 2010)
Defining management and organization -- Open versus closed systems -- Service quality approach -- Environmental influences -- Conflict, power, and ethical issues -- Motivation -- Leadership -- Communication -- Police administration -- Courts -- Probation and parole -- Prisons, jails, and detention centers -- Security management -- Measuring organizational effectiveness and service quality